Analisis Sistem Informasi Akuntansi Penjualan Kredit Pada Dealer Motor Honda PT Pratama Metropolis Sejahtera - Nadya Aprilia Fauzian; Amin Sadiqin (CV ODIS, 2021)
Accounting plays an important role for every company in monitoring the course of financial flows and sales and can be a reference in lowering the level of risk that will occur in the future. Accounting itself must also be applied into information systems to get effective results and good reports. With the accounting information system owned by PT Pratama Metropolis Sejahtera, the company gets an effective report in knowing the flow of cash and credit sales that are structured. In the journal that will be discussed by this author there are several conclusions that can later be a reference about the importance of accounting information systems in the company.